2015
DOI: 10.1016/j.jaci.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

TH9 cells are required for tissue mast cell accumulation during allergic inflammation

Abstract: Background IL-9 is important for the growth and survival of mast cells. IL-9 is produced by T cells, NKT cells, mast cells, eosinophils, and innate lymphoid cells, although the cells required for mast cell accumulation during allergic inflammation remain undefined. Objective To elucidate the role of Th9 cells in promoting mast cell accumulation in models of allergic lung inflammation. Methods Adoptive transfer of OVA-specific Th2 and Th9 cells was used to assess the ability of each subset to mediate mast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(158 citation statements)
references
References 50 publications
7
149
0
2
Order By: Relevance
“…Importantly, while we and others have shown that the HDM model of airway inflammation is dependent on IL-17 (22, 43), the OVA-alum model is largely IL-17 independent (44), so that the effects of ETV5-deficiency on IL-17 should not impact the total cellular inflammation in our studies. Both ETV5 and PU.1 contribute to the ability of Th9 cells to promote accumulation and gene expression of mast cells in lung tissue, again consistent with our previous results on the role of Th9 cells in mast cell accumulation in multiple models of allergic airway disease (45). We did observe that IL-13-producing T cells in the lung were also decreased in mice with T cells lacking both ETV5 and PU.1, though the proportion of these cells was not different, suggesting the decrease in number was linked to decreased overall inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, while we and others have shown that the HDM model of airway inflammation is dependent on IL-17 (22, 43), the OVA-alum model is largely IL-17 independent (44), so that the effects of ETV5-deficiency on IL-17 should not impact the total cellular inflammation in our studies. Both ETV5 and PU.1 contribute to the ability of Th9 cells to promote accumulation and gene expression of mast cells in lung tissue, again consistent with our previous results on the role of Th9 cells in mast cell accumulation in multiple models of allergic airway disease (45). We did observe that IL-13-producing T cells in the lung were also decreased in mice with T cells lacking both ETV5 and PU.1, though the proportion of these cells was not different, suggesting the decrease in number was linked to decreased overall inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Among these, the CD4-Cre should only affect expression in NKT cells. We previously suggested that PU.1 was not required for IL-9 production by NKT cells (45), but it is not clear if ETV5 might play a role within these cells. The role of NKT cells in asthma models is still debated, and what controls IL-9 within these cells is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…IL-25 secretion by epithelial tuft cells also may aid the expansion of type 2 innate lymphoid cell (ILC2) populations 174 , which together with T H 2 cells secrete cytokines that promote the T H 2 cell-mediated immune response 175 , which includes tissue eosinophil accumulation and IgE class-switching by B cells 20 . T H 9 cells also contribute to the allergic immune response by increasing tissue mast cell accumulation 176 , and IL-4-mediated signalling may convert regulatory T cells into T H 2 cells 62 . The roles of follicular T cells, tissue-resident T cells, CD8 + T cells and γδ T cells remain to be determined.…”
Section: Figurementioning
confidence: 99%
“…For example, in an OVA model, enhanced mast cell accumulation followed adoptive transfer of T H 9 cells but not T H 2 cells, and this effect was dependent on T cell–derived IL-9. 136 Analysis of T H 9 cells in relation to asthma phenotypes in human subjects could shed more light on their role.…”
Section: Heterogeneity Of T Cells and Influence Of The Tissue Microenmentioning
confidence: 99%